2022
DOI: 10.3389/fonc.2022.881496
|View full text |Cite
|
Sign up to set email alerts
|

MiR-320b and miR-320d as Biomarkers to Predict and Participate in the Formation of Platinum Resistance in Ovarian Cancer Patients

Abstract: Patients with ovarian cancer who receive platinum-based chemotherapy typically develop platinum resistance, which leads to tumor recurrence and mortality. Therefore, finding the underlying mechanisms and biomarkers is critical. A total of 51 platinum-resistant and 70 platinum-sensitive ovarian cancer patients were enrolled in this study. We examined the GSE131978 dataset in the National Center for Biotechnology Information (NCBI) Gene Expression Omnibus database for differentially expressed long non-coding RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Among these 12 m 7 G-miRNAs, four belong to the miR-320 family, known for anti-oncogene target miRNA for cancer therapy ( Liang et al, 2021 ). Notably, miR-320b and miR-320d were identified as prediction biomarkers for platinum resistance in ovarian cancer patients ( Liu et al, 2022 ). Aberrant expression of miR-320e, let-7a-5p and miR-92b-3p have been acknowledged as a prognostic biomarker in colorectal cancer ( Perez-Carbonell et al, 2015 ; Pichler et al, 2017 ; Bustos et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these 12 m 7 G-miRNAs, four belong to the miR-320 family, known for anti-oncogene target miRNA for cancer therapy ( Liang et al, 2021 ). Notably, miR-320b and miR-320d were identified as prediction biomarkers for platinum resistance in ovarian cancer patients ( Liu et al, 2022 ). Aberrant expression of miR-320e, let-7a-5p and miR-92b-3p have been acknowledged as a prognostic biomarker in colorectal cancer ( Perez-Carbonell et al, 2015 ; Pichler et al, 2017 ; Bustos et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These members also exhibited the capability to activate ADSCs, though less effectively than miR-320a. Prior research has indicated potential associations between miR-320b and miR-320d and platinum resistance in OC patients [ 47 ]. Furthermore, plasma exosomal miR-320d has shown promise as a noninvasive and effective diagnostic biomarker for OC [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the research reports mentioned above on the effects of hsa-miR-320d on the relative cancers showed that the relative effects of hsa-miR-320d were altogether negatively oncogenic, as hsa-miR-320d was a potential tumor suppressor. [114,117–127] The expression of hsa-miR-320d was significantly decreased in the cancer tissue and/or the peripheral serum of patients, [114,117–119,123,124,126] which was a loss of negative effect of hsa-miR-320d as a potential tumor suppressor. A lower expression level of hsa-miR-320d, either in cancer tissue or in peripheral serum, was positively correlated with the related tumorigenesis and development, adverse tumor phenotypes or prognosis, like bigger tumor size, advanced clinic stages, lymph node metastasis, chemoresistance, recurrence, or shorter overall and disease-free survival, etc.…”
Section: Discussionmentioning
confidence: 99%
“…As to hsa-miR-320d in cancers, there have been several special research reports, like on colorectal cancer, [117][118][119][120][121] on lung cancer, [122] on HCC, [114] on ovarian cancer, [123,124] on prostate cancer [10,125] and on chordoma. [126,127] But, until now, there is not any special research report on the potential values of exosomal hsa-miR-320d in the EC clinic and the relative research.…”
Section: The Potential Values Of Exosomal Hsa-mir-320d In Ecmentioning
confidence: 99%
See 1 more Smart Citation